Effects of sintering conditions on phase formation and dielectric properties of 0.8Pb (Zr1/2Ti1/2) O3-0.2Pb(Co1/3Nb2/3)O3ceramics - A. Prasatkhetragarn (2018)
The influences of sintering conditions on dielectric properties of the 0.8Pb(Zr1/2Ti1/2)O3 -0.2Pb(Co1/3Nb2/3)O3 ceramics have been investigated with sintering temperatures of 1175, 1200°, 1225, and 1250°C and dwell times for 2, 6, and 10 hours. The crystal structure of dense specimens showed coexistence between tetragonal, rhombohedral and pseudo cubic phases in all sintering temperatures, while tetragonal-rich phase appeared with increasing dwell times. A maximum dielectric constant was observed at sintering condition of 1200°C for 2 hours, while the transition temperature slightly increased with increasing dwell time. All ceramics also showed diffused phase transition behaviors with a minimum diffusivity at sintering condition of 1200°C for 2 hours. Copyright © Taylor & Francis Group, LLC.